GaN-Based Metal-Insulator-Semiconductor High-Electron-Mobility Transistors Using Low-Pressure Chemical Vapor Deposition SiNx as Gate Dielectric - Mengyuan Hua; Cheng Liu; Shu Yang; Shenghou Liu; Kai Fu; Zhihua Dong; Yong Cai; Baoshun Zhang; Chen, Kevin J. (IEEE electron device letters, 2015)
In this letter, silicon nitride (SiNx) film deposited at 780 °C by low-pressure chemical vapor deposition (LPCVD) was employed as gate dielectric for GaN-based metal-insulator-semiconductor high-electron-mobility transistors. The LPCVD-SiN x exhibit improved gate dielectric performance than the plasma enhanced chemical vapor deposition-SiN x , including smaller forward and reverse gate leakage, and higher forward gate breakdown voltage.